Definiendo el concepto del Incremento Material del Riesgo en la relación de causalidad: ¿podría aplicarse en el Derecho peruano? - Canepa Casillas, Ricardo (2020)
Through this essay, the author attacks the issues behind the evidentiary gaps that prevent the finding of a causal link between the damage and the wrongdoer, particularly when these evidentiary gaps preclude the claimant from proving who, within a group of persons who have increased the risk of damage, actually caused it. As a solution, the author proposes that the “multiple tortfeasor exception”, which is an application of the “material increase in risk” developed in the common law, can be implemented in Peru thanks to the flexibility provided by the adequate cause (the Peruvian approach to causation). For these purposes, the lessons learned through the common law shall serve as guiding light.